Gravity-magnetic appraisal of the southern part of the Cauvery Basin, Eastern Continental Margin of India (ECMI): evidence of a volcanic rifted margin - Ganguli, Shuva Shankha; Pal, Sanjit K. (Frontiers in Earth Science, 2023)
The Cauvery sedimentary basin of India, a part of the Eastern Continental Margin of India (ECMI), has evolved as a consequence of its break up from East Antarctica in the early Cretaceous. The study covers ~ 10,000 km 2 in the southern part of the Cauvery basin. A total of 5161 gravity-magnetic observations were made in an area bounded by 78 o -79 o E longitude and 9 o -10 o N latitude. The gravity anomaly map shows a dominant NE-SW trend with a total relief of 83 mGal from -77 mGal to 6 mGal. The map reveals a very prominent NE-SW trending linear gravity high bands and two circular/elliptical gravity lows around Madurai and Ramanathapuram respectively. The residual gravity map reveals NE-SW trending alternative bands of